Relationship between RNA polymerase I activity and ornithine decarboxylase in rat liver tissues. - Urata, M (1987)
In order to examine the relationship between RNA polymerase I and ornithine decarboxylase (ODC), three lines of experiments were performed, with the following results. The glucocorticoid-induced increase of RNA polymerase I in rat liver nuclei was not abolished by administration of inhibitors of ODC synthesis and activity, namely 1,3-diaminopropane and 2-difluoromethylornithine respectively. Anti-ODC antibody did not cross-react with RNA polymerase I solubilized from rat liver nucleoli, indicating the absence of a common protein sequence in these enzymes. The ODC preparation which was treated with transglutaminase in the presence of putrescine could not stimulate the activity of RNA polymerase I in nuclei of liver and prostate. All these results suggest that the increases in ODC protein or activity are not a prerequisite to the increase in RNA polymerase I after hormonal or physiological stimuli, but rather that the increases in both enzymes are separate responses to the primary stimuli.